The rain’s language, by Julieta Pinto, as a metaphoric interiority of the subject - Alvarado Vega, Óscar Gerardo (2022)
This text shows the metaphoric manifestation of rain in The rain’s language (2000) by Julieta Pinto, as a direct correspondence with Lucia, the main character´s being and her becoming, and how the symbolism of her name is related with encounters and discounters surrounding her life. The girl/woman´s life is posed in a harmonic relation with nature and her existing divergence with the city´s world.